Structural changes of dilated pelvic ureters in adults - Neves,Fernando (2014)
PURPOSE: To perform a quantitative assessment of different types of pelvic ureter tissues with chronic dilation in adults, using stereological methods. METHODS: We analyzed fragments of dilated pelvic ureters obtained from 6 patients aged between 35 and 67 years (mean, 46 years) who underwent ureteral reimplantation surgery for different reasons. The obstruction duration ranged from 27 to 180 days (mean, 93 days). The control group included fragments of normal pelvic ureters obtained during nephrectomy in 7 kidney transplant donors (age: range, 25-51 years; mean, 36 years). The volumetric density of collagen in the ureter, elastic fibers, and smooth muscle fibers was assessed. RESULTS: The volumetric density (Vv) of collagen showed no significant difference between the two groups (control: 45.3 ± 6.1; dilated: 40.8 ± 6.9; P = 0.23). A statistically significant increase in Vv of elastic fibers was observed in the dilated ureters (control: 18.4 ± 1.2; dilated: 24.6 ± 5.4; P = 0.03). A statistically significant increase in the Vv of smooth muscle fibers was observed in the dilated ureter (control: 42.0 ± 6.0; dilated: 56.2 ± 6.1; P = 0.001). CONCLUSION: The chronically dilated pelvic ureters had significantly more elastin and smooth muscle contents than the controls.